Development of Big Book Media Based on Augmented Reality Material on Structure and Function of Plant Parts for Class IV SDN Tlogo 02 Blitar - Zahro, Sitna Fatimatus; Amalia, Shofi Nur; Oktaviani, Ragil Tri (Journal of Educational Sciences, 2024)
The aim of this research is to determine the validity, feasibility and attractiveness of big book learning media based on augmented reality on the structure and function of plant parts for class IV SDN Tlogo 02 Blitar Regency. This type of research uses Research and Development (RnD) with the ADDIE development model which has five stages, namely Analyze, Design, Develop, Implementation, Evaluation. The subjects of this research were 27 class IV students at UPT SDN Tlogo 02. The data collection techniques used in this research included interviews, questionnaires and documentation. This questionnaire is aimed at expert validators to test the validity of the media, teacher responses to test the suitability of the media, and student responses to test the attractiveness of the media being developed. The results of this research showed that the validity of big book media based on augmented reality material on the structure and function of plant parts obtained a total percentage of 88.18% with very valid criteria. Eligibility has a final score of 100% with very feasible criteria. The attractiveness of the big book media based on augmented reality regarding the structure and function of plant parts has a final score of 93.15% with very interesting criteria.